Hubungan Hubungan Pengetahuan dan Pola Konsumsi Produk Minuman Herbal dengan Kejadian Dismenore Pada Remaja Putri: The Relationship Between Knowledge and Patterns of Herbal Drink Product Consumption with Dysmenorrhea of Female Adolescent - Cintadea Herviana; Farapti Farapti (Amerta Nutrition, 2023)
Background: Adolescence is when there is a sex change, both primary and secondary. In adolescent girls, the primary sex change is marked by the arrival of menstruation. Dysmenorrhea is pain that is felt during the menstrual process. Several types of non-medical therapy can be used to treat dysmenorrhea, including herbal drink products. Objectives: This research analyzed the relationship between knowledge and herbal drink product consumption patterns with dysmenorrhea of female adolescents in Pondok Pesantren Subulussalam Surabaya. Methods: This research was an analytical observational study with the cross-sectional method. This study's population was young women living in Pondok Pesantren Subulussalam Surabaya, Indonesia. The research sample was taken using the census sampling method where the population was sampled, namely 49 students. Data were collected by interview using a knowledge questionnaire of herbal drink products, the SQ – FFQ questionnaire, and the Numeric Rating Scale questionnaire. Results: From the research that has been done, the results showed that the average age of the research respondents was 14 years six months, and as many as 85.7% of respondents have normal menarche age, as many as 26.5% of respondents have long menstrual periods, as many as 30.6% of respondents know it is classified as lacking, and 75.5% of respondents have a consumption pattern of herbal beverage products with a seldom category. Conclusions: There was a relationship between knowledge of herbal drink products and the incidence of dysmenorrhea, but there was no relationship between consumption patterns of herbal drink products and the incidence of dysmenorrhea.